PERENCANAAN DAN PERANCANGAN PESANTREN TAHFIDZUL QUR’AN AGRO - Asshofa'an, Ahmad; Rudiyono, Rudiyono; Alhamdani, Muhammad Ridha (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Tahfidzul Qura'an Agro Islamic Boarding School is an area that provides formal Islamic education (Madrasah Aliyah) and non-formal education of tahfidz Al-Qu'an and agriculture. The design location is in Kubu Raya Regency. Islamic Boarding School Tahfidzul Qura'an Agro is not only a place to learn religious knowledge but can also be a place to learn agriculture because the agricultural sector is the leading sector in Kubu Raya Regency. This design is also motivated by the number of memorizers of the Qur'an which is small compared to the Muslim population in Indonesia. Â The purpose of this design is to be able to design a Tahfidzul Qur'an Islamic boarding school facility to meet the needs in the field of religious education and other skills in the world of work. As a Thafidzul Qur'an boarding school, the students are required to memorize the Qur'an because the main function of this pesantren is to increase the number of memorizing the Qur'an. Skills in agriculture are also taught to equip students to face the world of work. The stages in the planning and design of the Tahfidzul Qura'an Agro Islamic Boarding School start from the idea stage, data collection, analysis, synthesis, pre-design, and design development. The pesantren area of the Tahfidzul Qura'an Agro Islamic Boarding School consists of several masses, namely: mosque buildings, memorization facilities, schools, student dormitories, management housing, and agricultural facilities. The mosque building is a focal point in the area. The mosque is in the middle to separate the zoana of male and female students. The location of the mosque is also in the middle so that it is easily accessible by students and residents around the pesantren area. memorizing facilities and schools are on the right and left of the mosque. The dormitory and residence manager are at the back to get a quieter atmosphere.